Improved electric-field-induced strain and strong photoluminescence properties in novel Er3+-modified 0.93Bi0.5Na0.5TiO3-0.07BaTiO3 multifunctional ceramics. Issue 10 (15th May 2022) - Zhao, Shuaijie; Zhang, Yangyang; Zhang, Qingfeng; Li, Hui; Gao, Jingxia; Li, Mingyang; Zhang, Wenfeng; Liu, Junna; Yang, Baocheng
Abstract: Recently, the progress of electronic devices toward miniaturization has strongly promoted development of multifunctional materials possessing multiple desirable properties. In this study, we develop and fabricate 0.93Bi0.5 Na0.5 TiO3 -0.07BaTiO3 - x Er multifunctional ceramics which show simultaneously considerable electric-field-induced strain and bright green light emission properties. With the introduction of Er 3+, the ceramics gradually transform from non-ergodic relaxor phase to ergodic relaxor phase which could reversibly transform to ferroelectric phase under the electric field. As a result, with improving Er 3+ content, the shape of the polarization-electric field loops of the ceramics become pinched, and it is obvious that the negative strain disappears while the positive strain gradually increases and reaches a maximum value 0.46% at x = 1.2 mol%. Besides, After the ceramics are poled, the light emission peak are greatly enhanced attributed to the decreased crystal symmetry and increased domain size, and is the strongest at x = 1.2 mol%. These results indicate that 0.93Bi0.5 Na0.5 TiO3 -0.07BaTiO3 - x Er ceramics are good candidates for developing multifunctional optoelectronic devices.